Efficacy of an emollient cream in the treatment of xerosis in diabetic foot: a double‐blind, randomized, vehicle‐controlled clinical trial. (23rd January 2017) - Martini, J.; Huertas, C.; Turlier, V.; Saint‐Martory, C.; Delarue, A.
Abstract: Background: Peripheral neuronal impairment compromises foot health in patients with diabetes. Clinically, xerosis is the most common mild complication, but it should not be underestimated. An effective treatment must be able to restore the cutaneous barrier and prevent water loss, to maintain adequate hydration and protection. Objective: This study aimed to assess the efficacy of an emollient cream on foot xerosis in patients with diabetes. Methods: This is a prospective, multicenter, randomized, double‐blind contralateral vehicle‐controlled study in 57 patients with diabetes. Patients were treated twice daily for 27 ± 2 days with the study emollient containing glycerol 15%, liquid and soft paraffin 10%, glycerol monostearate, stearic acid, polydimethylcyclosiloxane, silicone oil, macrogol 600, trolamine, propyl parahydroxybenzoate and purified water (Dexeryl ® ; Pierre Fabre Medicament, Boulogne, France) or its vehicle (glycerol monostearate, stearic acid, polydimethylcyclosiloxane, silicone oil, macrogol 600, trolamine, propyl parahydroxybenzoate and purified water). Efficacy was assessed after a 28‐day treatment period using a validated score [Xerosis Assessment Scale (XAS) score], instrumental measurements and subjective assessment. Results: The XAS score decreased to 3.2 ± 2.6 points with the emollient and 4.1 ± 2.3 with the vehicle ( P = 0.001). Improvement was observed from day 14 ( P = 0.012). Compared with the vehicle, the emollient also significantly improved the overall skin score, hydration index, D‐Squame ® (CuDerm Corporation, Dallas, TX, USA) test, skin roughness and patients' opinions. Conclusion: Treatment with an emollient is effective for improving foot xerosis in patients with diabetes.